Annelid-inspired high-elongation origami robot using partial material removal. (1st January 2023) - Wei, Xianhe; Zhao, Yanzhi; Fan, Zhengwei; Guo, Zhifeng; Han, Zhen; Shan, Yu; Liu, Zhixin
Abstract: Existing soft robots face challenges given the need for an improved flexible robot elongation rate, bending angle and movement flexibility in space target acquisition, disaster search and rescue, unknown environment detection and other fields. Yoshimura tubular origami shows good applied performance with regard to the axial elongation ratio. However, due to the characteristics of nonrigid folding and a negative Poisson's ratio, the axial elongation length and bending angle of the Yoshimura tubular origami mechanism are limited. Annelids show highly flexible body movement. By analyzing the main factors limiting the axial elongation rate of the Yoshimura tubular origami mechanism and imitating the morphological characteristics and motion mechanism of annelid somite joints, we proposed a method to achieve high flexibility and large angle bending of a tubular origami mechanism based on local material removal and macroscopic elimination of the negative Poisson's ratio. Combined with a Ni–Ti memory alloy wire segmented driving scheme based on force constraints and geometric constraints a continuous origami robot is designed. The optimal cutting amount of the origami mechanism is determined by experiments, and the maximum elongation ratio and bending angle of the origami mechanism reach 2.5 and 3 times those before material removal, respectively. The paper folding module unit was solved in a kinematic analysis workspace. Finally, a prototype was used to verify the performance and demonstrate the application potential of the robot in an unstructured rescue scene.